Theoretical study, simulation & fabrication on dry oxidation in terms of Si02 layer thinckness, resistivity & surface roughness - Mohd Adam Alias
This final year project focused on four goals and the aims for the project are: to study the dry oxidation process and characteristics, to grow a thin layer of Silicon oxide (SiO2), to determine the better parameter for dry oxidation, and to prepare a result as the reference for future experimental.